Imagining His Dark Materials as a Gesamtkunstwerk. Issue 2 (31st August 2007) - MacDonald, Laura
Using first-hand interviews conducted with playwright Nicholas Wright and composer Jonathan Dove, this article discusses the adaptation and production process behind the Royal National Theatre's staging of His Dark Materials. It suggests that an interdisciplinary, collaborative approach was essential in bringing Pullman's epic to the stage. Different combinations of dialogue, music, scenic design, staging and puppetry allowed the production to convey detailed character histories and complex emotional experiences, and cover vast geographies, distilling the essence of the compelling epic. In leaving the structure of the interdisciplinary collaboration transparent, this article argues that the director, Nicholas Hytner, and his team invited the audience to enter the worlds of the play as participants in the collaborative work, free to mould their own experience of the heroes' adventures, and complete the adaptation with their own imagination. This twenty-first-century Gesamtkunstwerk bears comparison with Wagner's Ring cycle of music dramas.